Influence of Hypodynamia on Joints and Synovial Membranes in Hypothyroidism Syndrome and Morphological Features of Synovial Membranes - Abdullaevich, Rasulov Khamidulla; Dustmurodovna, Eshonkulova Bahriniso; Jumaevich, Butaev Chori; Anvarovich, Nuraliev Abror (American Journal of Biomedicine and Pharmacy, 2025)
According to the World Health Organization (WHO), 75% of the world’s population suffers from diseases of the musculoskeletal system. This epidemic situation has been studied for many years in scientific research in the field, linking it to various causes. Some scientists link diseases of the musculoskeletal system to abnormal fetal development, others to hereditary predisposition, and another group of researchers to ecology and lifestyle.